1990 sonrası Türkiyede yaşanan finansal krizlerin T.C.M.B. bilançoları ile analizi - Akan, Serkan (My University, 2004)
1990 Sonrası Türkiye'de Yaşanan Finansal Krizlerin Merkez Bankası Bilançoları ile Analizi başlıklı tez çalışmam üç bölümden oluşmaktadır. Birinci bölümde genel olarak ekonomik kriz, oluşmasındaki nedenler ve ekonomik krizlerin türleri hakkında bilgi verilmektedir. İkinci bölümde, 1990 yılı sonrası Türkiye'de yaşanan finansal krizler ve nedenleri üzerinde durulmaktadır. Son bölüm ise, finansal krizlerin Merkez Bankası bilançoları ile analizini içermekte ve bir karşılaştırma imkanı sunmaktadır.

In the study titild analysing the financial prister expericent in Turkey after 1990'sby the heart of the Centrak Bank balance sheets is exist of 3 chapters.in the first chapter, the information about the economic cirisis in general the reasons that cause it and the types of the economic crisis is given in the second chapter, the financial crisis experient and reasons of it in Turkey, after the year 1990 is thiscusts. The last chapter, consists of the central bank balance sheets and its analysis of economic crises andinforming as on the past and teacher experinces of the particularities of crisis in Turkey .
Keywords: Ekonomi; Ekonomik durum ve koşullar; Ekonomik Krizler